A cross-national analysis of PhD models. Issue 3 (10th July 2020) - Dominguez-Whitehead, Yasmine; Maringe, Felix
Abstract : Purpose: This paper provides a cross-national analysis of PhD supervision models, milestones and examination procedures in order to compare PhD programs and their practices. Design/methodology/approach: A comparative approach is employed, which systematically interrogates PhD supervision models, milestones and examination procedures in the United Kingdom, South Africa and the United States via a comprehensive review of the practices and literature. Findings: The findings indicate the ramifications of the different approaches and highlight the benefits and drawbacks associated with the different models. Originality/value: By making explicit the dominant supervision models, milestones and examination procedures that exist in the United Kingdom, South Africa and the United States, the authors shed light on the somewhat obscure path to earning a PhD degree.